Wójt jako lokalny lider. Wady i zalety reformy gminnej – rozważania prawno-polityczne - Matyjek, Sebastian (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The article focuses on the problem of the mayor as a local leader and describes the reform of the municipal which was introduced in 2002. Thesis in divided into three parts. In the first part author defines mayor as a local leader in the local government. In the second part article describes comparison on the collegiate community board with mayor and also author writes about advantages and disadvantages of this system. Another problem is conflict of the executive and the legislative body. In the following part we can read about limit term mayor in municipalities. The last chapter is reflections and conclusions on the introductions of direct executive authority in polish law and suggestions tending to remove the pathology in relation mayor – the municipal council.